Musculoskeletal disorder (MSDS) risk factors in construction workers at PT. Aluphi Hijau Lumina Dhoho Kediri International Airport Project in 2024 - Mardian, Okbi; Ariyanto, Januar; Putri, Aragar; Purnamawati, Dewi (Institute of Computer Science (IOCS), 2025)
Musculoskeletal disorders (MSDs) are a major contributor to disability worldwide, being the leading cause of disability in 160 countries. A review of 9,482 workers in 12 regions found that MSDs were the leading impact on workers in 16%. To analyze the most important factors on the risk of MSDs in construction workers of PT. Aluphi Hijau Lumina at the Dhoho Kediri International Airport Project in 2024. Analytical observational research with a cross-sectional study approach. aims to see the relationship between independent variables and dependent variables, namely individual characteristics (age, length of service, BMI/body mass index, smoking), ergonomic factors such as work posture (Total Back Exposure Static, Total Back Exposure Moving, Shpulder Arm Exposure, Wrist & Hand Exposure, Neck Exposure, Driving Exposure, Vibration Exposure, Work Pace Exposure, & Stress Exposure), workload, and duration of work time on complaints of musculoskeletal disorders (MSDs). The results of the study showed no relationship between individual characteristics (Age, Length of Service, BMI and Smoking Status) with MSDs complaints in Construction workers with P Value of age = 0.110; length of service = 0.597; BMI = 0.228; smoking status = 0.451. There was no relationship between ergonomic factors of body posture (Total Back Exposure Static, Total Back Exposure Moving, Total Wrist Hand Exposure, Total Driving Exposure, Total Vibration Exposure, Total Work Pace Exposure, Total Stress Exposure) & duration of work of construction workers with MSDs complaints in Construction workers of PT. Lumina Green Aluphi with p value Total Back Exposure Static = 0.960; Total Back Exposure Moving = 0.286, Total Wrist Hand Exposure = 0.344; Total Driving Exposure = 0.512; Total Vibration Exposure= 1,000, Total Work Pace Exposure= 1,000, Total Stress Exposure= 0.316. There is a significant relationship between Total Shoulder Arm, Total Neck Exposure, & Workload of construction workers with MSDs complaints in construction workers of PT. Aluphi Hijau Lumina with Total Shoulder Arm p value= 0.005, Total Neck Exposure p value= 0.040, & Workload p value= 0.005. The most influential variable on MSDs complaints is neck exposure with a P value of 0.026, OR = 6.9. The risk of experiencing pain complaints in construction workers' activities with neck positions is 7 times more at risk of experiencing MSDs complaints. There is a need to be modified of work equipment with a working position with a bent neck condition, which can be done with engineering control on changes to work stations or work methods or setting the time for work exposure with an awkward position that is too long.